2023
DOI: 10.1007/s10811-023-02943-y
|View full text |Cite
|
Sign up to set email alerts
|

Pavlova gyrans as a potential source of essential fatty acids, sterols and pigments: culture under low temperature

Abstract: Haptophytes are emerging as sustainable sources of high-value metabolites such as polyunsaturated fatty acids (PUFAs). The goal of this work was to isolate a native haptophyte from the southwestern Atlantic coast and to evaluate the effect of low-temperature stress on the production of PUFAs, sterols, and pigments during its cultivation. The strain was identi ed as Pavlova gyrans. Cultures were carried out in a photobioreactor for 10 days at 20°C (Control), lowering the culture temperature to 10°C at the begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In the microalgae Pavlova gyrans, a native haptophyte from the southwestern coast of the Atlantic Ocean, it was shown that the highest percentage of bound sterols was found at the early stages of its cultivation (on the 2nd day). However, by the end of cultivation (the 9th day), under the influence of low-temperature stress, the proportion of free sterols increased significantly [31]. The properties of plant cell membranes, including those under low-temperature stress, are affected by changes in the ratio between campesterol, stigmasterine, and β-sitosterol [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the microalgae Pavlova gyrans, a native haptophyte from the southwestern coast of the Atlantic Ocean, it was shown that the highest percentage of bound sterols was found at the early stages of its cultivation (on the 2nd day). However, by the end of cultivation (the 9th day), under the influence of low-temperature stress, the proportion of free sterols increased significantly [31]. The properties of plant cell membranes, including those under low-temperature stress, are affected by changes in the ratio between campesterol, stigmasterine, and β-sitosterol [32].…”
Section: Discussionmentioning
confidence: 99%